2011
DOI: 10.1182/blood-2010-10-315507
|View full text |Cite
|
Sign up to set email alerts
|

Tmprss6 is a genetic modifier of the Hfe-hemochromatosis phenotype in mice

Abstract: The hereditary hemochromatosis protein HFE promotes the expression of hepcidin, a circulating hormone produced by the liver that inhibits dietary iron absorption and macrophage iron release. HFE mutations are associated with impaired hepatic bone morphogenetic protein (BMP)/SMAD signaling for hepcidin production. TMPRSS6, a transmembrane serine protease mutated in iron-refractory iron deficiency anemia, inhibits hepcidin expression by dampening BMP/SMAD signaling. In the present study, we used genetic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 50 publications
3
63
1
Order By: Relevance
“…The fact that Nrf2 -/-mice fed iron-rich diet develop marked liver injury despite a similar hepatic iron loading to wild-type animals is of great relevance because although the liver is particularly exposed to the toxic effects of iron in excess, rodents are generally resistant to iron-induced liver injury. Mouse models of HH develop the spontaneous iron overload phenotype seen in human patients without developing significant iron-induced liver injury [27,28]. Likewise, the supplementation of mouse diets with carbonyl iron is generally well tolerated, despite the substantial increase in hepatic iron [5,29].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Nrf2 -/-mice fed iron-rich diet develop marked liver injury despite a similar hepatic iron loading to wild-type animals is of great relevance because although the liver is particularly exposed to the toxic effects of iron in excess, rodents are generally resistant to iron-induced liver injury. Mouse models of HH develop the spontaneous iron overload phenotype seen in human patients without developing significant iron-induced liver injury [27,28]. Likewise, the supplementation of mouse diets with carbonyl iron is generally well tolerated, despite the substantial increase in hepatic iron [5,29].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this has been shown in mouse models. 83 However, from the limited number of studies available, TMPRSS6 SNPs do not seem to modulate iron accumulation in hemochromatosis patients.…”
Section: Resultsmentioning
confidence: 99%
“…In theory TFR2 might promote BMP-SMAD signaling for hepcidin production by inhibiting the activity of TMPRSS6, as was hypothesized for HFE, 32 by up-regulating BMP6 or through other unknown mechanisms. For this reason we compared the effect of Tmprss6 inactivation in mice with a total deletion of Tfr2 (Tfr2 We found that in adult Tfr2 -/-mice the heterozygous loss of Tmprss6 slightly reduces the severity of hepatic iron overload and partially reverts the hematologic phenotype, reducing hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%